Beef Production in the Southwestern United States: Strategies Toward Sustainability - Spiegal, Sheri; Cibils, Andres F.; Bestelmeyer, Brandon T.; Steiner, Jean L.; Estell, Richard E.; Archer, David W.; Auvermann, Brent W.; Bestelmeyer, Stephanie V.; Boucheron, Laura E.; Cao, Huiping; Cox, Andrew R.; Devlin, Daniel; et al. (Frontiers in Sustainable Food Systems, 2020)
From grazing lands to meat packing, beef production systems in the United States are increasingly expected to meet new global demand without compromising environmental quality. These challenges and opportunities are manifest in the American Southwest and Ogallala Aquifer region, neighboring regions connected ecologically and socially through beef production. Each year most calves raised on extensive, arid Southwestern pastures are exported to the Ogallala Aquifer region for finishing on grains from the American Upper Midwest. Intensifying changes in climate, vegetation, and human demographics threaten the sustainability of the system. Heritage cattle genetics, precision ranching, and range finishing on Southwestern rangelands are three promising strategies for improving sustainability. However, major knowledge gaps exist. Desirable landscape use by Raramuri Criollo, a heritage cattle type, has been identified in several arid rangeland settings, but little is known about their performance in conventional feedyards. While precision agriculture is already prevalent in croplands, less is known about how these technologies can be cost effective in arid rangelands. Moreover, many perceive range finishing as environmentally friendly, but tradeoffs of greenhouse gases, increased rangeland use, and disruption of Ogallala Aquifer cattle feeding systems must be assessed. Here we introduce a new USDA-NIFA Coordinated Agricultural Project designed to fill these knowledge gaps and advance sustainability. With a boundary-spanning approach of education, participatory research, and extension, the project is identifying tradeoffs of the three strategies with explicit attention to pericoupling of the two adjacent regions and full consideration of the coupled ecological and social systems across those regions.